2021
DOI: 10.26719/emhj.21.032
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the most common processed foods consumed by Iranian children

Abstract: Background: The trend of increasing overweight and obesity among children is a huge burden on health systems. In this regard, the growing availability of processed foods, often energy dense and nutrient poor, has become a major concern. Changing this trend will require evidence-based policies. Aims: This systematic review aimed to identify the most common processed/ultraprocessed foods consumed by 4–12-year-old Iranian children. Methods: We searched PubMed, Scopus and Web of science, as well as Persian scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Several studies have explored sex-related differences www.nature.com/scientificreports/ in dietary intake. For example, the VYRONAS study 38 reported a preference for cereals and cereal products, especially for breakfast by boys aged 12-17 compared to their female counterparts. This likely reflects the higher need for foods that contribute more energy during rapid growth in boys.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored sex-related differences www.nature.com/scientificreports/ in dietary intake. For example, the VYRONAS study 38 reported a preference for cereals and cereal products, especially for breakfast by boys aged 12-17 compared to their female counterparts. This likely reflects the higher need for foods that contribute more energy during rapid growth in boys.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, links have been established between increased ultra-processed food consumption, early onset of NCDs and decreased quality of life in children and adolescents [7,9,14,27]. Childhood obesity is becoming increasing common in Iran where children are overconsuming processed food containing high amounts of sugar and/or fats [16].…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence showed links between ultra-processed food intake and excessive free sugar intake. Babashahi et al [16] showed processed sugar and sweets, followed by oils, biscuits and cakes, were the most commonly consumed processed food groups in a systematic review and meta-analysis of 10 studies on 67,093 Iranian children aged 4-12 years. Other countries have shown similar results; for example, Machado et al [30] showed that ultra-processed food consumption drives an excessive free sugar intake among all age groups in Australia.…”
Section: The Impact Of Ultra-processed Foods On Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Cakes, sweet biscuits and pastries had the highest share among not permitted foods. Also, these food items have a large share of processed food products that Iranian children consume on a daily basis [58]. A crosssectional study in Kerman, a province in central Iran, also pointed to the low compliance of food products available in school buffets with national guideline [40].…”
Section: Discussionmentioning
confidence: 99%